Exercise Guidelines to Promote Cardiometabolic Health in Spinal Cord Injured Humans: Time to Raise the Intensity? - Richard Metcalfe (Archives of Physical Medicine and Rehabilitation, 2017)
Spinal cord injury (SCI) is a life-changing event that, as a result of paralysis, negatively influences habitual levels of physical activity and hence cardiometabolic health. Performing regular structured exercise therefore appears extremely important in persons with SCI. However, exercise options are mainly limited to the upper body, which involves a smaller activated muscle mass compared with the mainly leg-based activities commonly performed by nondisabled individuals. Current exercise guidelines for SCI focus predominantly on relative short durations of moderate-intensity aerobic upper-body exercise, yet contemporary evidence suggests this is not sufficient to induce meaningful improvements in risk factors for the prevention of cardiometabolic disease in this population. As such, these guidelines and their physiological basis require reappraisal. In this special communication, we propose that high-intensity interval training (HIIT) may be a viable alternative exercise strategy to promote vigorous-intensity exercise and prevent cardiometabolic disease in persons with SCI. Supplementing the limited data from SCI cohorts with consistent findings from studies in nondisabled populations, we present strong evidence to suggest that HIIT is superior to moderate-intensity aerobic exercise for improving cardiorespiratory fitness, insulin sensitivity, and vascular function. The potential application and safety of HIIT in this population is also discussed. We conclude that increasing exercise intensity could offer a simple, readily available, time-efficient solution to improve cardiometabolic health in persons with SCI. We call for high-quality randomized controlled trials to examine the efficacy and safety of HIIT in this population.